Metabolomics, Metabonomics and Functional Nutrition: The Next Step in Nutritional Metabolism and Biotherapeutics - Larry H. Bernstein (Journal of Pharmacy and Nutrition Sciences, 2012)
Metabonomics is the newest member of the convergent "-omics" family. This multi-parametric technique is used for studying metabolites in biological fluids for the purpose of metabolic profiling for biomarker and diagnostic applications, and to study the effects of environmental stimuli (diet, weight loss, exercise) and other therapeutic applications (lifestyle modification and drug effects) on the metabolome. Metabonomics has the advantage for defining biological phenotypes, but has a close relationship to investigation of the proteome, driven by advances in NMR and MS. The technique has proved highly informative in applications that include toxicology, pharmacology, and the biomedical sciences. This review elaborates on the paradigm shift that is emerging from this discovery process.